Fauna de mosquiteiros (Diptera: Culicidae) em fragmento de caatinga no Alto Sertão Sergipano - Cruz, Danilo Esdras Rocha (2013)
The family Culicidae has great public health importance for being composed by haematophagous insects in majority, which can be vector of diseases for the human being and other vertebrates. The knowledge about culicideos fauna, besides of data about various species that compose the Caatinga biome, can also bring information about species that are vector of pathogens, providing important tools in case of eventual epidemic outbreak at the region. The Caatinga biome occupies around 55% of all northeast region, representing 11% of Brazil s surface, and holds the position of the less preserved biome of the country, relative to its total area. This work aimed to realize a mosquitoes fauna survey, as well as ecologic aspects analysis for adult species in two areas of Caatinga and immature in three semi permanent breeding grounds. The study was realized in the city of Poço Redondo, semi-arid of Sergipe, where the Unidade de Conservação Monumento Natural Grota do Angico is located under exclusive domain of Caatinga. Collects were made monthly in two areas of Caatinga, between 5 p.m. and 8 p.m. using the Shannon trap for adults, and in three breeding grounds with plastic dipper method for mosquito larvae collects. On ecologic aspects analysis were used the Shannon diversity index, Pielou s equitability, Berger-Parker dominance, Nonmetric multidimensional scaling (NMDS) for species composition. A number of 1788 specimens were collected on total among adults and immature, distributed on ten genus, Aedes, Aedomyia, Anopheles, Coquilettidia, Culex, Haemagogus, Mansonia, Ochlerotatus, Psorophora and Uranotaenia and 21 species. The adults resulted in 583 specimens, 268 from shrubby Caatinga and 315 from arboreal Caatinga, dominant species were Mansonia (Man) indubitans and Ochlerotatus (Och) scapularis,there was no difference between these areas on species composition or abundance, however, the arboreal Caatinga was richer in species. In relation to the immature, breeding sede captured the larger number of specimens (N=590), followed by breeding cancela (N=436) and the smaller value on breeding trilha (N=179). Species composition did not show difference between breedings, dominant species were Anopheles (Nys) albitarsis and Culex (Cx) chidesteri. The presence of mosquitoes species with vector importance, some of that capable to adapt on anthropic ambient, associated with lack of knowledge about Caatinga s mosquitoes suggests future studies to avoid epidemiologic outbreaks in the Unidade de conservação Monumento Natural Grota do Angico .